Safety distance between underground natural gas and water pipeline facilities - Mohsin R.; Majid Z.A.; Yusof M.Z. (Elsevier Ltd, 2023)
A leaking water pipe bursting high pressure water jet in the soil will create slurry erosion which will eventually erode the adjacent natural gas pipe, thus causing its failure. The standard 300 mm safety distance used to place natural gas pipe away from water pipeline facilities needs to be reviewed to consider accidental damage and provide safety cushion to the natural gas pipe. This paper presents a study on underground natural gas pipeline safety distance via experimental and numerical approaches. The pressure-distance characteristic curve obtained from this experimental study showed that the pressure was inversely proportional to the square of the separation distance. Experimental testing using water-to-water pipeline system environment was used to represent the worst case environment, and could be used as a guide to estimate appropriate safety distance. Dynamic pressures obtained from the experimental measurement and simulation prediction mutually agreed along the high-pressure water jetting path. From the experimental and simulation exercises, zero effect distance for water-to-water medium was obtained at an estimated horizontal distance at a minimum of 1500 mm, while for the water-to-sand medium, the distance was estimated at a minimum of 1200 mm. © 2014 Elsevier Ltd.